NEW OPPORTUNITIES OF PROPHYLAXIS OF BRONCHIAL ASTHMA EXACERBATIONS IN CHILDREN WITH ACUTE RESPIRATORY INFECTION - V.N. Chernyshov; A.A. Savis’ko; A.A. Lebedenko (Вопросы современной педиатрии, 2010)
The data on pidotimod (Imunorix) effectiveness in prophylaxis of bronchial asthma exacerbations in children are analyzed. Authors’ trial included 55 children 5–10 years old with exacerbations of a disease caused by acute respiratory infections. Authors studied influence of pidotimod on antioxidant system of blood serum. The effectiveness of the drug for the prophylaxis of respiratory infections in children with bronchial asthma was shown, and this effect favored to the decrease of rate of exacerbations.Key words: children, bronchial asthma, prophylaxis, pidotimod.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(2):54-57)